PENINGKATAN KESEHATAN TERNAK GUNA MENJAGA KESTABILAN NILAI JUAL SAPI DI DESA DARMASARI, KECAMATAN SIKUR, KABUPATEN LOMBOK TIMUR - Syifa, Aulia; Santriawan, Lalu Djamika; Olga, Kadek Soni; Hw, Lalu Husnan Afif; Zahroti, Meri; Besari, Doyang; Rosalinda; Amrullah, Yayan; Rukmana, I Nyoman Agus Aryadie (Jurnal Wicara, 2024)
Livestock health is one of the factors that influence the success of cattle farming in West Nusa Tenggara Province. One of the areas that has the potential for livestock development in NTB is Darmasari Village, Sikur district, East Lombok Regency. One of the problems that occurs in the village is that farmers do not maintain the health of livestock properly so that losses can occur as seen from the low knowledge of livestock health management. The purpose of the livestock posyandu is to improve the welfare of farmers through animal health and provide knowledge to farmers in livestock health management. Several methods of activities were carried out, including the preparation stage starting from surveys and observations, the implementation stage which consisted of briefings by the Animal Health and Livestock Services, group divisions, and healthy injection activities, and the final stage was carried out, namely the evaluation of activities. The results of the activities carried out include (1) briefing conducted by the Livestock and Animal Health Service Office represented by the Head of the Animal Health Division, (2) group division, (3) livestock health services carried out include giving vitamins and medicines to livestock, (4) evaluation carried out after the Livestock Posyandu activity is completed. With the livestock posyandu activities carried out routinely and continuously, it is expected to minimize the negative impact of livestock diseases so that the quality of livestock health increases and the selling price of livestock in the market is higher